Istanbul memories and the city - Pamuk, Orhan 1952- (Knopf, 2005)
A portrait, by turns intimate and panoramic, of one of the world's great cities, by its foremost man of letters. Blending reminiscence with history; family photographs with portraits of poets and pashas; art criticism, metaphysical musing, and, now and again, a fanciful tale, Pamuk invents an ingenious form to evoke his lifelong home, the city that forged his imagination. He begins with his childhood, his first intimations of the melancholy awareness of living in the seat of ruined imperial glories, in a country trying to become "modern" at the crossroads of East and West. Against a background of shattered monuments, neglected villas, ghostly backstreets, and, above all, the fabled waters of the Bosphorus, he charts the evolution of a rich imaginative life, which furnished a daydreaming boy refuge from family discord and inner turmoil, and which would continue to serve the famous writer he was to become. --From publisher description.
Originally published as İstanbul : hatiralar ve şehir. - "A Borzoi book"
Keywords: Pamuk, Orhan <1952->; Pamuk, Orhan -- 1952-; Geschichte 1900-2000; Geschichte 1952-1972; Geschichte 1952-2000; Geschichte 1950-1970; Geschichte 1900-1960; Geschichte 1955-1960; Authors, Turkish -- 20th century -- Biography; Gesellschaftsleben; Kultur; aIstanbul (Turkey) -- xDescription and travel; Türkei; Istanbul; Autobiografie; Erlebnisbericht